Indigenous media and social media convergence: adaptation of storytelling on Twitter, SoundCloud and YouTube - Mpofu, Phillip (Journal of Asian and African Studies, 2022)
Storytelling is ordinarily trivialised as an antiquated oramedia genre, and of less significance in Zimbabwean mainstream media and communication studies, hence it is understudied. Recent studies largely take a literary gaze on storytelling, and do not theorise it from an indigenous media viewpoint or appreciate its convergence with social media. Drawing on concepts of media convergence and the digital public sphere, this netnographic study examines the adaptation of storytelling on Twitter, SoundCloud and YouTube, focusing on patterns of production, delivery, participation, language forms, reception and audiences. The article shows inventive re-embodiment and adaptation of storytelling on online spaces, that is, the endurance and remaking of indigenous media in the context of new media and communication technologies. The manifestation of the folktale narrative style on social media exhibits the rise of a secondary form of orality recreated, reproduced and applied in the digital form and on social media. While digital and social media are perceived as threatening the continued existence of indigenous media, this article attests social media as breathing spaces for indigenous media.